A Game Dimension Function - Önal, Süleyman; Soyarslan, Servet (Topology Proceedings, 2021)
We define a topological game dimension, (gd), such that gd(X) = Ind(X) where X is a hereditarily normal space and Ind(X) ≤ gd(X) where X is a normal space. We ask a question which is about whether gd(X) = Ind(X) where X is a normal space. By making some appropriate modifications in this game, the dimension functions Ind and ind can be characterized in the realm of normal spaces.